Dampak Kejadian Bencana terhadap Upah Tenaga Kerja di Indonesia - Rismawati, Rismawati; Handayani, Dwini (https://jurnal.binamandiri.ac.id/, 2025)
Natural disasters cause loss of life and infrastructure damage. Over the past decade, the frequency and number of natural disaster events have tended to increase. Such events can threaten and disrupt community life, including the education sector, lead to the loss of jobs and assets, cause health and psychological problems, and disrupt economic activities. Disasters also result in damaged infrastructure, weakened social cohesion, and increased poverty rates. One of the variables affected by disasters is labor wages. The determinants of wages are classified into three categories: 1) demographic characteristics, including age, age squared, gender, marital status, and place of residence; 2) human resource characteristics, including education, certified training, and work experience; and 3) job characteristics, including working hours and industry sector. This study utilizes data from the 2019 National Labor Force Survey (Sakernas) and the Indonesia Disaster Information Data (DIBI) from BNPB. The findings indicate that disaster events significantly affect labor wages in Indonesia, although the estimated effect is relatively small. The policy implication of this study is that policymakers can enhance community resilience through both structural and non-structural mitigation efforts to reduce the adverse impacts of disasters, particularly their impact on the wages of affected workers.